Negotiation of Meaning of Indonesian EFL Learners in Casual Conversation: An SFL Study - Fadhila Yonata (Universitas Islam Negeri Raden Mas Said Surakarta, 2021)
Communicative interaction is demanded by all levels of EFL learners. To prepare them to comply with this purpose, engaging them to deal with the real-life conversation using the target language may have beneficial effects on their second language acquisition process. However, the way learners negotiating meaning in an understandable way and how they position themselves as the appropriate role of the speakers are still rarely studied, especially in the Indonesian teaching and learning context. This study aims to reveal what type of commodity is being exchanged by graduate learners (3 females and 1 male) when they are assigned to have an unplanned casual conversation. The study further analyzes the nature of the exchange structure of EFL learners’ casual conversation seen from the Systemic Functional Linguistics perspective. The data were taken from audio recordings of casual conversations and then transcribed as the written data. The conversation was then divided into clauses as the unit of analysis. In employing a spoken discourse analysis framework, interactive analysis was implemented to discover exchange structure. The results show the exchanged commodity is information through statements. It indicates that as magister students, they always show their knowledge off, and intimacy sometimes matters as the reason for informative conversations. The speakers’ role also has been successfully achieved by the speakers since their ability to position themselves as initiators or responders to keep the conversational flow.